Evaluation of Traditional and Pictorial Symptom Scores among Indian Men with Lower Urinary Tract Symptoms: A Retrospective Observational Study - Eeshansh Khare (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: The traditional questionnaire for Lower Urinary Tract Symptoms (LUTS) in males is the International Prostate Symptom Score (IPSS). To minimise its limitations, a picturebased Visual Prostate Symptom Score (VPSS) was developed as an alternative. Aim: To compare the ease of use, applicability, and clinical correlation of the Traditional Symptom Score (TSS) and Pictorial Symptom Score (PSS) among Indian men presenting with LUTS. Materials and Methods: This was a retrospective, recordbased observational study conducted on 100 male patients with LUTS in the Outpatient Department (OPD) of the Urology Department at Vivanta Critical Care and Multispeciality Hospital, Chhindwara, Madhya Pradesh, India, from January 2024 to December 2024. The first 50 patients were given the IPSS questionnaire to complete, followed by the VPSS, and were considered Group I; the next consecutive 50 patients who completed the VPSS first and the IPSS later were considered Group II. Evaluation parameters were age, education status, time taken for filling symptom scores, help needed for filling symptom scores, prostate-specific antigen, prostate size, and uroflowmetry parameters. Unpaired t-test, Chi-square test, and Pearson’s correlation test were used in statistical analysis. Results: The majority of patients, 16 (32%) in Group I and 20 (40%) in Group II, were aged 61-70 years. 29 (58%) in group I and 16 (32%) in group II had an average educational status of primary education and below. Thirty-two patients in group I completed the PSS without help, but only 15 in group II completed the TSS without help. 12 patients had difficulty completing the PSS, compared with 38 for the TSS. Difficulty faced by patients was understanding the scoring systems of each question and the questions asked in questionnaires. Mean Prostate-specific antigen (PSA) in group I and II was 2.46±1.5 ng/ mL and 2.17±1.35 ng/mL, respectively. Patients with increased prostate size had a higher total score in group I (r=0.91) and group II as well (r=0.90). PSA also showed a positive correlation with both scores (r=0.83 and r=0.76, respectively). Both TSS and PSS showed a negative correlation with maximum flow rate (r = -0.60 and r = -0.76, respectively). Conclusion: The PSS was easier for patients to complete than the traditional symptom score. The severity of LUTS was strongly correlated with both symptom scores. Maximum urinary flow rate inversely correlated with both symptom scores.